Women as Articulations of Nation-Space and an Agency of Insularity: An Analysis of Selected Films by Jeffrey Jeturian - Tan, Katrina Ross A. (Review of Women's Studies; Vol 20 No 1-2 (2010): Review of Women's Studies Volume XX, Numbers 1-2 (January-December 2010))
This essay focuses on three of Jeffrey Jeturian’s films: Pila Balde (1999), Tuhog (2001), and Kubrador (2006). It follows Roland Tolentino's analysis of the Brocka films but focuses on the trope of the female characters, as it suggests discussing the films as articulations of the nation-space in which women characters are the primary trope to map the discourse on nation; the analysis emphasizes the intersection of gender and nation.